META ANALYSIS: THE EFFECT OF IMPLEMENTATION OF FLIPPED CLASSROOM MODEL ON STUDENT’S HIGHER ORDER THINKING SKILLS (International Conference on Social and Islamic Studies, 2022)
The purpose of this study was to determine the effect of the Flipped Classroom model on higher order thinking skills. The method used in this study is a quantitative method with a meta-analytic research design. Data collection was carried out by researchers by searching for publication articles that were relevant or related to the topics to be studied on internet network sites in the form of Google Scholar, Google Scholar, Researchgate, OneSearch, Microsoft Academia, Academia, and Repositories. The sampling technique used purposive sampling technique. The instrument used is a data code sheet that summarizes data and data information. Data were analyzed by calculating the effect size value using the standardized means difference formula. Based on the results of the analysis it is known that the Flipped Classroom model as a whole is effective (significant) in improving students' high-level thinking skills, found 7 publication articles with a mean effect size of 2.225 and belonging to the very large category, the Flipped Classroom model based on the year of publication is effective (significant) in improve students' higher order thinking skills. Thus the Flipped Classroom model is recommended to be applied to higher education learning.